Effect of suspended uncontaminated sediment on persistent organic pollutant release. (18th December 2013) - Handlin, Mzuri; Molina, Andrew; James, Nicole; McConville, Megan; Dunnivant, Frank
Abstract The transport and fate of persistent organic pollutants (POPs) during resuspension events were investigated using a batch mixing technique. This technique allowed for the determination of sorption and desorption kinetics under more realistic mixing conditions than those used in previous investigations. It was demonstrated that sorption follows second‐order kinetics that are dependent on both POP concentration and the total suspended solids (TSS) of the system. Desorption shows a similar dependence. To further characterize pollutant release, the impact on maximum POP release of suspending uncontaminated sediment concomitantly with contaminated sediment was investigated, as this more accurately models real‐world resuspension events. It was found that even relatively low ratios of uncontaminated to contaminated sediment (1:2) yield a maximum POP release nearly 10 times lower than for systems containing only contaminated sediment. Increasing the ratio of uncontaminated sediment further reduced maximum POP release. These results highlight an important limitation of laboratory desorption experiments and current risk‐assessment models related to dredging operations; under typical field conditions, the impact of dredging on pollutant transport and fate may be greatly overpredicted. Environ Toxicol Chem 2014;33:375–381. © 2013 SETAC